Physics for you - Johnson, Keith (Cheltenham, England : Stanley Thornes (Publishers) Ltd, 1996)
To accommodate the latest National Curriculum requirements this physics textbook has new pages and extra questions added. The book contains a character called Professor Messer who is always making mistakes and students are invited to put him right.
Donation from the Asia Foundation/ Savar Campus
Keywords: Physics -- Problems, exercises, etc; Physics -- Pure science